Rebel on the Canal: Disrupted Trade Access and Social Conflict in China, 1650–1911 - Cao, Yiming; Chen, Shuo (American Economic Review, 2022)
This paper examines the effects of the abandonment of China’s Grand Canal—the world’s largest and oldest artificial waterway—which served as a disruption to regional trade access. Using an original dataset covering 575 counties over 262 years, we show that the canal’s abandonment contributed to the social turmoil that engulfed North China in the nineteenth century. Counties along the canal experienced an additional 117 percent increase in rebelliousness after the canal’s closure relative to their non-canal counterparts. Our findings highlight the important role that continued access to trade routes plays in reducing conflict. (JEL D74, N75, N95, O18, O22, R12, R42)